2021
DOI: 10.7860/jcdr/2021/47171.14473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plyometrics and Pilates Training on Dynamic Balance and Core Strength of Karate Players

Abstract: Introduction: The success of the karate player mainly depends on the balance and core strength. Improvement in these physical variables depends upon the type of exercise training used by the athletes. In the Indian context, there is lack of literature that supports the use of Pilates and Plyometric Training (PT) programme in training of Karate players. Therefore, to achieve success in the sport, best training method should be chosen by athletes or coaches. Aim: To compare and evaluate the effectiveness of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…The total number of studies obtained 45% of the total scale score (15 points), which can be seen in Table 1 . Two studies obtained a score of 10/15 [ 26 , 27 ], two obtained 9/15 [ 28 , 29 ], two obtained 8/15 [ 30 , 31 ], five obtained 7/15 [ 32 , 33 , 34 , 35 , 36 ], four obtained 6/15 [ 37 , 38 , 39 , 40 ], two obtained 5/15 [ 41 , 42 ], and three obtained 4/15 [ 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The total number of studies obtained 45% of the total scale score (15 points), which can be seen in Table 1 . Two studies obtained a score of 10/15 [ 26 , 27 ], two obtained 9/15 [ 28 , 29 ], two obtained 8/15 [ 30 , 31 ], five obtained 7/15 [ 32 , 33 , 34 , 35 , 36 ], four obtained 6/15 [ 37 , 38 , 39 , 40 ], two obtained 5/15 [ 41 , 42 ], and three obtained 4/15 [ 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were carried out on the continent of South America, Europe, Asia, and Africa, specifically six in Brazil [ 28 , 29 , 31 , 32 , 33 , 36 ], two in Lithuania [ 34 , 45 ], two in Spain [ 26 , 27 ], one in Serbia [ 38 ], one in Denmark [ 44 ], one in France [ 37 ], one in India [ 41 ], one in Turkey [ 30 ], one in Iran [ 39 ], one in Korea [ 40 ], one in China [ 35 ], and one in Egypt [ 43 ], respectively. Regarding the OCS practiced, seven studies were interventions with judo [ 28 , 29 , 31 , 33 , 36 , 37 , 38 ], five studies with karate [ 27 , 30 , 39 , 43 , 44 ], five with boxing [ 32 , 34 , 35 , 40 , 45 ], two with wrestling [ 41 , 42 ], and one study with fencing [ 26 ]. No articles were found that met the inclusion criteria for the taekwondo modality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations